Rulfo photographer, more than a personal universe (2022)
To speak of Juan Rulfo is to exalt a literary figure, whose fame crossed borders with only two books, Pedro Páramo and El llano en llamas. In these volumes the national aspect appeared as an obligatory reference. However, there is another area in Rulfo’s work where the aesthetics of photography come to the fore. Despite his artistic quality, he considered himself an amateur photographer; he never wanted to share credits with the great masters of that time in México, such as Lola or Manuel Álvarez Bravo, Nacho López or Kati Horna. Locating his images together with his literature gives us an enriched vision of Rulfo. In this space, it is about showing a Rulfo photographer who expresses himself in images that are at the height of his books.